Assessment of Ectomycorrhizal Fungal Diversity in a Suburban Secondary Forest in the Northwestern Part of Tama Area, Tokyo - Shirakawa, Makoto; Ishikawa, Akira; Fuchigami, Takurou; Tanaka, Megumi (Journal of the Japanese Forest Society, 2022)
To assess ectomycorrhizal (ECM) fungal diversity in a suburban secondary forest, we surveyed sporocarps, ECM root tips, and sclerotia in a Quercus serrata dominated site in Ome Forest, Tokyo, Japan. Using line census and plot sampling, 766 samples (436 sporocarps, 327 ECM root tips, and 3 sclerotia) were collected. Based on a morphological classification and analysis of internal transcribed spacer (ITS) rDNA sequences, 159 molecular operational taxonomic units, 41 distinct fungal genera, and 23 fungal families were identified, most of which belonged to Amanita, Boletaceae, Lactarius, Russula, Sebacina, and Tomentella. While these fungal species were common and widely distributed in the forest, other genera, such as Rhizopogon and Suillus, were distributed locally in various parts of the census route and plots. Our results revealed abundant diverse ECM-fungal species in a suburban secondary forest subject to anthropogenic disturbance. Furthermore, hierarchical clustering analysis using species data obtained by plot sampling indicated that locally distributed fungal species characterized the community composition of each plot, although the plots share common groups occurring at high frequency. Differences in stand type, anthropogenic disturbance, and microtopography may have affected these community compositions.